EFL secondary teachers’ pedagogical practice of motivational strategies through mentorship programs - Maharsi, Ista; Khotimah, Khusnul (Journal on English as a Foreign Language, 2025)
Previous studies have explored motivational strategies among ESL/EFL teachers in varied educational contexts. In contrast, mentorship programs that facilitate EFL teachers in developing their motivational strategies have drawn less attention. This study scrutinized EFL secondary teachers' motivational strategies after participating in a series of mentorship programs. Nested in action research, this study recruited three in-service teachers and sixty-three students from three vocational high schools in Indonesia. The teacher participants attended the mentorship program which encompassed training sessions and mentorship conferences. Data were collected from questionnaires, reflective journals, observations, and interviews. Data from the questionnaires were analyzed statistically using the t-test. The qualitative data obtained from reflective journals, observations, and interviews were analyzed using thematic analysis. This study reveals that teachers enacted varied motivational strategies catering to students' needs, which led to cultivating student motivation and learning engagement, especially for high achievers. Meanwhile, low achievers require more time and indicate more thoughtful treatment. The teachers positively perceived the mentorship and training program as instrumental in advancing their pedagogical practices. This study suggests practical recommendations for English teachers to enact motivational strategies to boost students' learning and sustain their motivation.